Politics in Leicestershire, c1677 to c1716 - Paterson, Neil Alasdair (2008)
This study has two principal aims. The first is to identify the characteristic features of Leicestershire’s politics at a time of turbulence in English political history and the second to examine the relationship between political activity at a local level and nationally. For the purpose of this study ‘politics’ is defined as the way individuals manoeuvred, intrigued and competed with rivals to maintain their personal position and secure political objectives. The focus therefore is on the way men behaved politically in a variety of formal and informal contexts. Five settings are used to examine this behaviour: the role played by the leading aristocrats and gentry, the appointment of local governors, the established church and non-conformity, parliamentary elections and the borough of Leicester.